The Efficacy of single dose prostaglandin F2? and anti-prostaglandin F2? antibodies in sheep - Risvanli, A.; Demiral, O.; Abay, M.; Saat, N.; Bekyurek, T.; Kulahci, F.; Balci, T. A. (Wiley-Blackwell Publishing, Inc, 2010)
[Abstract Not Available]
14th Annual Conference of theEuropean-Societies-Domestic-Animals-Reproduction/22nd Annual Meeting of the EU-AI-Vets -- SEP 15-22, 2010 -- Eger, HUNGARY